Patient-Centered Care and Psychiatric Rehabilitation: What’s the Connection? - Hensley, Melissa A. (International Journal of Psychosocial Rehabilitation, 2014)
Patient-centered care has become an increasingly popular concept in health care. Its applicability to psychiatric rehabilitation and recovery-oriented mental health services has been debated, especially because patient-centered care models often seem to continue reinforcing the traditional hierarchies of the medical system. However, many of the tenets of patient-centered care are potentially helpful in ensuring that service users’ voices are heard in the care delivery process, and can enrich our efforts to prioritize wellness and recovery.